A reabilitação psicossocial no atendimento em saúde mental: Estratégias em construção - Pereira, Maria Alice Ornellas [UNESP] (FapUNIFESP (SciELO), 2007)
This study aims to identify the representations about Psychosocial Rehabilitation by Mental Health professionals working in open services, and also the difficulties they have met in the process of turning the care effective for the population. The study uses a qualitative methodology, collecting data by means of semistructured interviews with 15 subjects. The professionals identify the rehabilitation process as complex, meeting several obstacles and requiring their dedication and a flexible attitude to achieve the expected results.
Psychosocial rehabilitation in mental health care: Strategies under construction
Keywords: Concept formation; Mental health; Social support; Brazil; concept formation; human; information processing; interview; mental disease; mental health; mental health service; personal autonomy; social support; Concept Formation; Data Collection; Humans; Interviews as Topic; Mental Disorders; Mental Health; Mental Health Services; Personal Autonomy; Social Support